Dosimetric properties of an environmental H*(10) dosemeter based on radiophotoluminescence of silver doped phosphate glass. (November 2020) - Assenmacher, Frank; Musto, Elisa; Yukihara, Eduardo G.
Abstract: The objective of this study was to investigate the energy and angle dependence of the RPL dosimetry system in use at the Paul Scherrer Institute (GBFJ-01 dosimeter, FGD 660 reader, and CDEC-Easy algorithm) for the operational dose quantity H *(10) and compare the results with the requirements from the Swiss dosimetry regulation. The energy response was determined for photon energies between 12 keV (N-15) and 1250 keV ( 60 Co) and the angle response was determined for 65 keV (N-80) and 662 keV ( 137 Cs). The data obtained in this study show that the RPL dosimeters satisfy the requirements of the Swiss dosimetry regulation for the energy dependence, but only partially satisfy the requirements for the angle dependence. For directional irradiations around ±90° the dosimeter response can deviate by more than the 20% allowed by the Swiss dosimetry regulation. If a more realistic testing scenario for the 90° irradiation is used, which includes full rotation of the dosimeter around its reference direction, the response is within 10% of the response at 0° irradiation. Full tests according to the IEC 62387 were not performed and, therefore, performance against this standard cannot be fully evaluated from this data. Nevertheless, the data indicate that the asymmetric dosimeter design would have difficulties satisfying the IEC 62387 standard for H *(10) for low energy photons and large angle irradiation, in spite of the allowance of full rotation for the 90° irradiations. Highlights: Energy and angle dependence of a radiophotoluminescence dosimetry system was investigated for environmental dosimetry. The dosimetric requirements of the Swiss radiation protection legislation are fulfilled for the energy dependence. The RPL relative response deviates by more than 20% for radiation incident with angles around 90°. Full rotation scenario proposed by the IEC 62387 for 90° irradiation improves the dosimeter response.